A Paradox in a Queueing Network with State-Dependent Routing and Loss. (5th November 2007) - Ziedins, Ilze
Abstract : Consider a network of parallel finite tandem queues with two stages, where each arrival attempts to minimize its own cost due to loss. It is known that the user optimal and asymptotic system optimal policies may differ—we give examples showing that they may differ for finite systems and that as the service rate is increased at the second stage the user optimal policy may change in such a way that the total expected cost due to loss increases.